PEMBUATAN MINYAK GOSOK BERBAHAN HERBAL VCO DAN JAHE - Ni Made Sukma Sanjiwani; Ni Putu Ayu Mirah Mariati; Agung Ari Chandra Wibawa; I Wayan Surya Rahadi; Dewa Ayu Sri Handani; I Wayan Sudiarsa (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
The problems faced by the Abasan community are that both young and old people often experience muscle aches and pains and have low knowledge of the use of herbal rubbing oil, as well as low interest in making their own herbal rubbing oil. Based on these problems, the community service team provided solutions in the form of socialisation on the use of herbal rubbing oil and teaching the community how to make herbal rubbing oil. This community service method is based on three areas. First, the production area: conducting lectures and discussions on what partners need so that the production process of herbal rubbing oil can run normally. Second, the management area: teaching participants how to make herbal rubbing oil that is good for health. Third, the marketing field, which involves teaching participants how to sell massage oil products at affordable prices so that many people will buy them by making the packaging and labels attractive. This community service activity took place on Sunday, 1 June 2025, at the Rare Asrama Banjar Abasan Early Childhood Education Centre. The event was attended in person by residents of Banjar Abasan, Singapadu Tengah Village, Sukawati Sub-district, Gianyar Regency, Bali. During the socialisation phase, the speaker was Mrs Ni Made Sukma Sanjiwani, S.Si., M.Si. Mrs Sukma explained the use of herbal ginger and VCO massage oil for health purposes. During the demonstration stage, conducted by lecturers and students, the lecturer taught participants how to make herbal massage oil using VCO and ginger. The initial step involved blending the ginger, then mixing it with a small amount of VCO, stirring it, and squeezing it. The ginger pulp was then mixed with a small amount of VCO and squeezed again. The ginger extract obtained is then mixed with mint oil and eucalyptus oil, with additional VCO added until the calibration mark is reached. The lecturer also labels the herbal massage oil bottles with stickers to improve the packaging, which can be used as an example for participants to make and sell the oil themselves, potentially turning it into their own business